Selection of name as a basic element of creating an associative image of a freight forwarding company - E. M. Tettsoeva; O. A. Tettsoeva (Вестник университета)
An important stage of a freight forwarding company positioning selection of its name, has been studied and the main principles of the name selection for an organization that is planning to operate in freight forwarding area have been revealed. Among requirements for a new company’s name non-conformity to widespread standards, relevance, presence of semantic charge, geographical conformability, sonority, originality, up-to-dateness and readiness for public use have been emphasized. The features of name selection for freight forwarding companies by reference to the specifics of the industry have been described in detail. Typical mistakes of owners of the companies operating in Russian freight forwarding market that are made when selecting a company’s name have been analysed.